The Marulić news: what have we learned about a Croatian classic over the last dozen years - Jovanović, Neven (2009)
New discoveries on Marko Marulić and his Latin opus in the last 15 years (unknown works, contribution to the Codex Traguriensis, digitisation of his works and books).